Digitalization of Business as a Method of Anti-Crisis Strategy During the Pandemic ("Journal "U". Economy. Management. Finance.", 2021)
In the conditions of the information society and the intensive development of modern digital technologies, changes are taking place in the field of business related to digitization. This article presents a study of the essence of digitalization and digital transformation of business models as interrelated phenomena.The essence of digital business transformation is well known, but not an approach to structured digital transformation of business models. In the article, digital transformation is considered as the process of integrating digital technologies into all aspects of business processes, requiring fundamental technological changes that create new products and services, operations and culture. The result of this research is conclusions about the benefits and risks of digital transformation for various companies, the main approaches to business implementation and the key drivers of digital transformation in business models.
Keywords: digital technologies; digital economy; digitalization; business model; transformation; crisis management